1988
DOI: 10.1038/bjc.1988.157
|View full text |Cite
|
Sign up to set email alerts
|

The effects of co-administration of selenium and cis-platin (CDDP) on CDDP-induced toxicity and antitumour activity

Abstract: Summary The therapeutic antitumour activity and host toxicity of cis-platin (CDDP), which was administered with selenium (sodium selenite) was studied on the growth of a human yolk sac tumour grown in nude mice. Treatment consisted of CDDP single agent chemotherapy (3 weeks) or preliminary PVB combination chemotherapy (CDDP+vinblastine +bleomycin, 2 weeks). Selenium was co-administered from day 1 to 5 with each therapeutic regimen. The administration of CDDP alone caused significant reduction in tumour burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 17 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Selenium (sodium selenite) can reduce cisplatin-induced toxicity without reducing the antitumor activity in mice bearing yolk sac and Prima breast tumors (36,37). Data from our laboratory demonstrate that MSC potentiate cell growth inhibition induced by SN-38, and the potentiation is associated with activation of GADD153, dephosphorylation of Akt, PARP cleavage, and induction of apoptosis.…”
Section: Introductionmentioning
confidence: 63%
“…Selenium (sodium selenite) can reduce cisplatin-induced toxicity without reducing the antitumor activity in mice bearing yolk sac and Prima breast tumors (36,37). Data from our laboratory demonstrate that MSC potentiate cell growth inhibition induced by SN-38, and the potentiation is associated with activation of GADD153, dephosphorylation of Akt, PARP cleavage, and induction of apoptosis.…”
Section: Introductionmentioning
confidence: 63%
“…These highly reactive oxygen species can cause extensive tissue damage through reactions with all biological macromolecule, e.g., lipids, proteins and nucleic acids, leading to formation of oxidized substances, such as MDA, which is the product membrane lipid peroxidation (Halliwell & Gutteridge 1993). In animals, renal and chromosomal damage due to cisplatin, other heavy metals and doxorubicin-induced cardiomyopathy can be prevented by supplementation with high doses of antioxidants, such as selenium, vitamins C and E, without compromising the anti-tumour activity (Wang et al 1980;Fujita et al 1982;Ohkawa et al 1988;Chorvatovicova et al 1991;Whanger 1992;Jotti et al 1993). For instance, Ohkawa et al (1988) have demonstrated in mice that selenium co-administration allows higher doses of cisplatin with reduction of nephro-and hematological toxicity, resulting in a higher therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, renal and chromosomal damage due to cisplatin, other heavy metals and doxorubicin-induced cardiomyopathy can be prevented by supplementation with high doses of antioxidants, such as selenium, vitamins C and E, without compromising the anti-tumour activity (Wang et al 1980;Fujita et al 1982;Ohkawa et al 1988;Chorvatovicova et al 1991;Whanger 1992;Jotti et al 1993). For instance, Ohkawa et al (1988) have demonstrated in mice that selenium co-administration allows higher doses of cisplatin with reduction of nephro-and hematological toxicity, resulting in a higher therapeutic index. Therefore, nutritional status of cancer patients, especially the nutritional intake of antioxidants and their concentrations in plasma and tissues may determine the extent of oxidative organ damage by free radicals produced by cytostatic drugs (Clemens et al 1990;Hay et al 1991;Forni & Armand 1994;Meyer & Madias 1994;Anderson et al 1995;Weijl et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Table II summarises extensive preclinical work that demonstrated the protective effects of various Se compounds against the toxicities of radiation (12, 36) and organ-specific toxicities of many cytotoxic drugs, including myelosuppression, mucositis, diarrhoea, alopecia, cystitis and nephrotoxicity (11, 13, 30, 37). Specific toxicities of cisplatin in kidneys, bone marrow and intestine were improved without affecting antitumour efficacy (30,(38)(39)(40)(41) or pharmacokinetics (42). Impressive protection from lethal effects of six cytotoxic drugs with 200 μg/day MSC was demonstrated in nude mice (13).…”
Section: Antitumour Efficacymentioning
confidence: 99%